2016
DOI: 10.1159/000446901
|View full text |Cite
|
Sign up to set email alerts
|

Memory and Spatial Cognition in Breast Cancer Patients Undergoing Adjuvant Endocrine Therapy

Abstract: Introduction: It is generally accepted that estrogens play a protective role in cognitive function. Therefore, it can be expected that subtotal estrogen deprivation following aromatase inhibition will alter cognitive performance. Methods: In a cross-sectional study we investigated 80 postmenopausal women with breast cancer. Memory and spatial cognition were compared across 4 treatment groups: tamoxifen only (TAM, n = 22), aromatase inhibitor only (AI, n = 22), TAM followed by AI (‘SWITCH group', n = 15), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In a small study of women, quite a long time after menopause, Arimidex for an average of 2 years (Berndt et al, 2016) caused significantly lower scores on general memory tests and attention and dramatically lower levels on verbal memory.…”
Section: Influence Of Ais On Cognitive Function In Womenmentioning
confidence: 98%
“…In a small study of women, quite a long time after menopause, Arimidex for an average of 2 years (Berndt et al, 2016) caused significantly lower scores on general memory tests and attention and dramatically lower levels on verbal memory.…”
Section: Influence Of Ais On Cognitive Function In Womenmentioning
confidence: 98%
“…We classified seven studies as considering attention an outcome and a cognitive domain possibly affected by the use of tamoxifen. These studies included objective measures that assess attention and concentration, 16,23 visual attention, 16,18,33,38,39 and distractibility 31 . The results of the studies investigating attention and concentration, visual attention, and distractibility generally suggested that tamoxifen does not negatively affect those skills 16,18,23,31,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…These studies included objective measures that assess attention and concentration, 16,23 visual attention, 16,18,33,38,39 and distractibility 31 . The results of the studies investigating attention and concentration, visual attention, and distractibility generally suggested that tamoxifen does not negatively affect those skills 16,18,23,31,38,39 . In fact, one study 38 suggested that women taking tamoxifen performed significantly better in tasks of attention/concentration compared to women taking AIs and also to women taking tamoxifen followed by AIs.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, there are - somewhat in contrast to the data of clinical trials - bothersome side effects, which are sometimes the cause for incompliance or change of treatment. Hot flashes, arthralgia, weight gain, grade 1 alopecia, or diminished cognitive function as investigated by Berndt et al [1] in this issue of BREAST CARE are reported by patients in daily clinical routine. …”
mentioning
confidence: 99%
“…In this issue Berndt et al [1] investigate the impact of endocrine treatment on cognitive function, in detail on memory and spatial cognition. They focused on these domains as there is evidence that they are influenced by 17β-estradiol.…”
mentioning
confidence: 99%